SURFACE WATER IMPACT ON A LARGE LUDZAS LAKE - Bule, Kristīne; Matisovs, Ivars (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2016)
The theme. Surface water impact on a Large Ludzas Lake. Problem statement. It is not known – what the lake surface water pollution affects the quality of the Lake Large Problems actuality. Ludza region data on the Lake Large Ludzas quality are not completely.